Silenced rivers - "McCully, Patrick" (New Delhi, 1998)
This book deals with the issues of mega dams. It is polemical in spirit and strongly opposes the construction of big dams. Using case studies from all over the world, including three case studies from India, the book addresses the important socio-political, ecological and developmental fallout. A seriously researched and well documented study.
Keywords: Dams